SYSTEMS APPROACH IN MILITARY PERSONNEL TRAINING TECHNOLOGY - Ryzhykov, Vadym; Buryi, Serhii; Kotova, Lina; Bondarenko, Oleksandr; Bura, Yuliia (Revista Inclusiones, 2020)
The article presents a theoretical and practical analysis of the theoretical foundations and technologies of practical application of the systems approach in the educational process of a military educational institution. The systems approach reduces most complex tasks to a project result that can be used to improve the quality of the decision in one or more major tasks. Prominent scholars and the founders of the systems approach as a method of scientific cognition included L. von Bertalanffy, A.A. Bogdanov, H. Simon, P. Drucker and A. Chandler who worked in the 1940- 50s. The systems approach was also developed and studied by such classical scholars as B.F. Lomov, B.G. Anaev, P.K. Anokhin, T. Kuhn, A. Makarenko, E. Laszlo and others. To fully expound the concept of the systems approach, one must clarify the "nature of the system itself", what the "system" means and how systems are implemented at different levels of the world of observation. For this study of the systematic approach to the technology of developing military education in the context of rapid development and growth of equipment and weapons, in our opinion, P.K. Anokhin’s definition of the "system" can be considered the most appropriate, "A system is a complex of inventive components, wherein interaction and interconnection take the form of interaction of components for obtaining a single focused result". This definition of a system fully corresponds to the analysis and synthesis of "artificial systems" in such a sphere of human activity as the specific educational process at a military educational institution.